2011
DOI: 10.1007/s00296-011-1896-9
|View full text |Cite
|
Sign up to set email alerts
|

QT dispersion in amyloidosis due to familial Mediterranean fever

Abstract: Cardiac amyloid deposition in FMF may cause increased QT dispersion (QTd), a marker for cardiac arrhythmias. The aim of this study was to further evaluate repolarization dispersion in familial Mediterranean fever (FMF) with amyloidosis. Findings on 12-lead electrocardiography were compared between 18 patients with FMF-amyloidosis and 18 age- and sex-matched control subjects. Repolarization and dispersion parameters were computed with designated computer software, and results of the 5 beats were subsequently av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…Furthermore, they reported that there is no significant difference in their similar studies of patients with FMF-amyloidosis, colchicine resistant-FMF, and FMF-responsive to colchicine, respectively. [21][22][23][24] Similar to our study, Topal et al 25 did not find any significant difference between the 35 uncomplicated FMF patients and the 38 healthy controls in terms of QTd.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, they reported that there is no significant difference in their similar studies of patients with FMF-amyloidosis, colchicine resistant-FMF, and FMF-responsive to colchicine, respectively. [21][22][23][24] Similar to our study, Topal et al 25 did not find any significant difference between the 35 uncomplicated FMF patients and the 38 healthy controls in terms of QTd.…”
Section: Discussionsupporting
confidence: 79%
“…However, further evaluation by our group did not reveal any difference in repolarization between FMF patients and healthy controls regardless of the development of amyloidosis [19,20].…”
Section: Introductionmentioning
confidence: 62%
“…Nussinovitchetal published several studies regarding cardiac repolarization abnormalities in FMF patients. In their studies, FMF patients with and without amyloidosis had similar repolarization indices (QT interval, QTc interval and QT dispersion) to those of healthy controls 5,11 . When colchicine resistant FMF patients were compared to healthy controls, they also revealed that cardiac repolarization indices were similar between the two groups 12 .…”
Section: Discussionmentioning
confidence: 99%
“…FMF may cause pericarditis due to serositis and/or cardiac amyloidosis as a part of the systemic disease 3 . Recent studies investigated repolarization abnormalities using markers such as QT dispersion, transmural dispersion of repolarization and P-wave dispersion in FMF patients with and without AAA [4][5][6] . Peak to end interval of T wave is newermarker of cardiac repolarization abnormality, which has been suggested as a better predictor of sudden cardiac death or ventricular tachycardia 7 .…”
mentioning
confidence: 99%